2015
DOI: 10.2967/jnumed.114.146662
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell–Mediated, Tumor Stroma–Targeted Radioiodine Therapy of Metastatic Colon Cancer Using the Sodium Iodide Symporter as Theranostic Gene

Abstract: The tumor-homing property of mesenchymal stem cells (MSCs) allows targeted delivery of therapeutic genes into the tumor microenvironment. The application of sodium iodide symporter (NIS) as a theranostic gene allows noninvasive imaging of MSC biodistribution and transgene expression before therapeutic radioiodine application. We have previously shown that linking therapeutic transgene expression to induction of the chemokine CCL5/ RANTES allows a more focused expression within primary tumors, as the adoptively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 42 publications
0
62
0
1
Order By: Relevance
“…MSCs spontaneously migrate to damaged tissue and are actively recruited to solid tumors (154). MSCs can be engineered to express NIS to selectively deliver radionuclides for better visualization and effective treatment of metastases.…”
Section: Nis As a Valuable Molecule To Monitor The Fate Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs spontaneously migrate to damaged tissue and are actively recruited to solid tumors (154). MSCs can be engineered to express NIS to selectively deliver radionuclides for better visualization and effective treatment of metastases.…”
Section: Nis As a Valuable Molecule To Monitor The Fate Of Stem Cellsmentioning
confidence: 99%
“…Indeed, NIS has been successfully used to detect and treat colorectal cancer metastases in rat liver in a model involving colorectal carcinoma LS174t cells injected into nude mice. When NIS-expressing MSCs were injected systemically into this model, 131 I − -treated mice displayed a 40% reduction in liver metastases when compared to control mice (154). …”
Section: Nis As a Valuable Molecule To Monitor The Fate Of Stem Cellsmentioning
confidence: 99%
“…128 MSCs have also been shown to be useful for the delivery of therapeutic genes in a colon cancer liver metastasis mouse model. 129 There are many other examples of MSCs being a potential vehicle for therapeutic delivery to tumors, including to brain tumors, 130 lung tumors, 131 hepatocellular carcinoma, 132 and prostate cancer. 133 These studies describe the use of MSCs for delivering not only therapeutic genes, but also therapeutic drugs and theranostic agents.…”
Section: Therapeutic Potential Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The short half-life and poor bioavailability of cancer-specific drugs are the key players that contribute to failure of current therapies. Recently, numerous studies have demonstrated the unique inherent tumor-tropic properties of stem cells including but not limited to mesenchymal stem cells (MSCs), neural stem cells (NSCs), and induced pluripotent stem cells (iPSCs) ( Jones, Lamb, Goldman, & Di Stasi, 2014;Knoop et al, 2015;Singh, Kalsan, Kumar, Saini, & Chandra, 2015;Stuckey and Shah, 2014). In addition, adult stem cells in their unmodified state have antitumor effects owing to factors that are released and physical interactions that are established between the stem cell and the tumor cell (Schichor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%